Food, place, and memory: Bangladeshi fish stores on Devon Avenue, Chicago. Issue 1 (2nd April 2016) - Sen, Arijit
ABSTRACT: This article explores the importance of food in the production of immigrant identity and placemaking in Chicago. The Bangladeshi fish stores located on Devon Avenue, Chicago, serve the unique culinary needs of immigrants from Bangladesh and Bengali-speaking regions of India. Based on interviews with store owners and customers and architectural analyses of these stores, this research explores how everyday engagements with food, specifically fish harvested in the delta region of Bangladesh, trigger cultural memories and reproduce particular forms of shopping practices and place identities among this relatively less-studied group of South Asian immigrants. This case study suggests that immigrant world-making is Janus-faced: simultaneously looking back and remembering the past while adapting to the present and reconstituting hybrid places in both societies of origin and settlement. An examination of this tension between past and present, near and far, local and global shows how diverse material contexts influence the way we interpret and invoke food memories. By tracing the trajectory of fish, this article demonstrates that food defines a variety of immigrant places—retail streets and grocery store aisles—as well as larger ecologies and spatial imaginaries, otherwise invisible in the studies of immigrant architecture.